VDC_100102371237.0X000001. Issue 10 (October 2018) - Yu, Alison J.; Inaba, Kenji; Biswas, Subarna; De Leon, Luis Alejandro; Wong, Monica; Benjamin, Elizabeth; Lam, Lydia; Demetriades, Demetrios
The objective of this study was to determine the survival outcome associated with large-volume blood transfusion after trauma. This was a retrospective study at a Level I trauma center from January 2000 to December 2014 that included trauma patients who received ≥25 units packed red blood cell (pRBC) within the first 24 hours of hospital admission. Univariate and multivariable logistic regressions identified risk factors for mortality. Receiver operating characteristic curve analysis evaluated the ability of pRBC volume to predict mortality. Among 74, 065 adults ( ‡ 18 years old), 178 patients (0.24%) received ≥25 units of pRBC in the first 24 hours, of which 142 (79.8%) received 25 to 49 units, 28 (15.7%) received 50 to 74 units, and 8 (4.5%) received ≥75 units. Overall, 92.2 per cent were male, mean age 33.9 (614.0), mean Injury Severity Score 28.9 (614.3), and median Glasgow Coma Scale score 12 (3–15). The overall mortality was 65.2 per cent and 64.1 per cent for those receiving 25 to 49 units, 64.3 per cent for 50 to 74 units, and 87.5 per cent for ≥75 units. In univariate analysis, female gender was associated with lower mortality [odds ratio (OR) 0.24, P = 0.025]. Decreasing Glasgow Coma Scale (OR 0.82, P < 0.001), increasing Injury Severity Score (OR 1.07, P < 0.001), and thoracotomy (OR 3.91, P < 0.001) were associated with higher mortality. There was no transfusion cutoff that was significantly associated with higher mortality.